Pengembangan Model Penerimaan Teknologi - Sukwadi, Ronald; Ambarita, Kevin Reinhard; Nguyen, Thi Bich Thu (Jurnal Tekno, 2021)
The world is developing exponentially and rapid. Industrial 4.0 is a milestone of industrial digitalization. Hence, the change of B2C business interaction with consumer. Annual growth of internet and smartphone users force industries such as creative industries to develop mobile application, This industry contributes 7.44% to national GDP in 2018 and is projected to be bigger each year. The growth of theatre count in Indonesia triggers film industries as part of creative industries to grow. TIX ID as an electronic ticketing keen on serving the best service quality to consumer through online purchases. From this phenomenon, researcher decided to identify the factors that will affect the adoption of TIX ID. This research employs an extended TAM which are Self-Efficacy and Subjective Norm. Questionnaires were distributed and a sample of 647 respondents was taken for analysis using SEM with AMOS. Findings of this study reveal that Self-Efficacy affects Perceived Ease of Use and Perceived Usefulness. Perceived Ease of Use affects Perceived Usefulness but doesn’t affect Attitude. Perceived Usefulness affects attitude and behaviour intention. Attitude and Subjective Norm affects behaviour intention.